(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 52 مريضا لديهم حاصة أندروجينية , تراوحت أعمارهم بين 19 و45 سنة بمعدل وسطي 31.35 سنة . قمنا بتقييم ومقارنة فعالية الفيناستيرايد الفموي (1 مغ/يومياً ) و محلول المينوكسيديل الموضعي 5% (مرتين يومياً ) لوحدهما و بالمشاركة بينهما . قسم المرضى إلى ثلاث مجموعات : تضمنت المجموعة الأولى 22مريضاً عولجوا بالفيناستيرايد الفموي وتضمنت المجموعة الثانية 18 مريضاً عولجوا بالمينوكسيديل الموضعي, أما المجموعة الثالثة فتضمنت 12 مريضاً عولجوا بالفيناستيرايد الفموي بالمشاركة مع المينوكسيديل الموضعي . قمنا بتقييم الفعالية وفق آليتين : التقييم الشخصي للمريض و التقييم السريري الفوتوغرافي . بعد 6 أشهر من العلاج وجدنا أن كلا من الفيناستيرايد الفموي1 مغ والمينوكسيديل الموضعي 5 % كان فعالا في علاج الحاصة الأندروجينية الخفيفة والمعتدلة عند الرجال ، من دون وجود فرق هام إحصائياً بينهما عند أخذ مدة الإصابة بالحاصة بالحسبان في المجموعتين الأولى و الثانية , إلا أن المشاركة بينهما أعطت نتائج أفضل في إعادة نمو الشعر عند المرضى, و استنتجنا من الدراسة أن الفعالية العلاجية تزداد بمشاركة الفيناستيرايد و المينوكسيديل , كما وجدنا أن الاستجابة للعلاج تكون أفضل كلما كانت مدة الإصابة بالحاصة الاندروجينية أقل . الآثار الجانبية كانت خفيفة ولم تستدع إيقاف العلاج , كما أنها تراجعت كلياً بعد توقف العلاج . Fifty-two men with AGA were enrolled in the study. The patients’ ages ranged from 19 to 45 years, with an average of 31.35 years. We evaluated and compared the efficacy of oral finasteride (1 mg/day), topical 5% minoxidil solution (twice daily) alone and in combination. The patients were divided into 3 groups: Group 1: oral finasteride (n =22). Group 2 : topical minoxidil (n = 18). Group 3: oral finasteride in combination with topical minoxidil (n =12) . We evaluated the patients on two bases: patients’ self-assessment, physician’s assessment by global photographic assessment. After a six-month treatment we found that both drugs were effective in the treatment of mild to moderate AGA, without a statistically significant difference between them if we considered the differences in the mean duration of alopecia between group 1 and 2. We also stated that subjects receiving finasteride in combination with minoxidil showed a better improvement in hair regrowth and concluded that the therapeutic efficacy is enhanced by combining the two drugs. We have also observed that the more recent the hair loss, the more success patients will have with the treatment. Adverse events were all mild; there was no need to stop the treatment, and these side effects disappeared as soon as the treatment was stopped.